Topology control in heterogeneous wireless sensor networks / Nafiseh Ahadi - Ahadi, Nafiseh (2011)
The most challenging issue in a wireless sensor network is energy consumption that affecting to lifetime of the WSN. Topology control algorithms are energy efficient mechanisms that extend lifetime of the WSN witch include tow processes, construction and maintenance. Topology control manages connectivity and coverage with the least active node with the goal of extending its lifetime. The sensors interact with each other via radio communications to the WSN gateway. Wireless nodes with uniform transmission ranges, homogeneous, are assumed in most of researches on topology control. Various types of power capacities, sensing and transmitting range, and computing/processing abilities are usually more practical for constructing highly reliable networks. In heterogeneous sensor networks communication is very diverse and nodes have different transmission range.